Nanoscale Thermosensitive Hydrogel Scaffolds Promote the Chondrogenic Differentiation of Dental Pulp Stem and Progenitor Cells: A Minimally Invasive Approach for Cartilage Regeneration - Talaat W (Dove Medical Press, 2020)
Wael Talaat,1– 3 Smriti Aryal AC,1,2 Sausan Al Kawas,1,2 AB Rani Samsudin,1,2 Nadia G Kandile,4 David RK Harding,5 Mohamed M Ghoneim,6 Waleed Zeiada,7,8 Jayalakshmi Jagal,2 Ahmed Aboelnaga,9 Mohamed Haider2,10,11 1Department of Oral and Craniofacial Health Sciences, College of Dental Medicine, University of Sharjah, Sharjah 27272, United Arab Emirates; 2Research Institute of Medical and Health Sciences, University of Sharjah, Sharjah 27272, United Arab Emirates; 3Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Suez Canal University, Ismaillia 41522, Egypt; 4Department of Chemistry, Faculty of Women, Ain Shams University, Heliopolis, Cairo 11757, Egypt; 5School of Fundamental Sciences, Massey University, Palmerston North 4442, New Zealand; 6Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Sinai University, Arish 45511, Egypt; 7Department of Civil and Environmental Engineering, College of Engineering, University of Sharjah, Sharjah 27272, United Arab Emirates; 8Public Works Engineering Department, College of Engineering, Mansoura University, Mansoura 35516, Egypt; 9Department of Surgery, Faculty of Medicine, Suez Canal University, Ismaillia 41522, Egypt; 10Department of Pharmaceutics and Pharmaceutical Technology, College of Pharmacy, University of Sharjah, Sharjah 27272, United Arab Emirates; 11Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo 71526, EgyptCorrespondence: Wael TalaatOral and Maxillofacial Surgery, College of Dental Medicine, University of Sharjah, Sharjah, United Arab EmiratesTel +971 65057605Fax +971 65057606Email wtaha@sharjah.ac.aePurpose: Several scaffolds and cell sources are being investigated for cartilage regeneration. The aim of the study was to prepare nanocellulose-based thermosensitive injectable hydrogel scaffolds and assess their potential as 3D scaffolds allowing the chondrogenic differentiation of embedded human dental pulp stem and progenitor cells (hDPSCs).Materials and Methods: The hydrogel-forming solutions were prepared by adding β-glycerophosphate (GP) to chitosan (CS) at different ratios. Nanocellulose (NC) suspension was produced from hemp hurd then added dropwise to the CS/GP mixture. In vitro characterization of the prepared hydrogels involved optimizing gelation and degradation time, mass-swelling ratio, and rheological properties. The hydrogel with optimal characteristics, NC-CS/GP-21, was selected for further investigation including assessment of biocompatibility. The chondrogenesis ability of hDPSCs embedded in NC-CS/GP-21 hydrogel was investigated in vitro and compared to that of bone marrow-derived mesenchymal stem cells (BMSCs), then was confirmed in vivo in 12 adult Sprague Dawley rats.Results: The selected hydrogel showed stability in culture media, had a gelation time of 2.8 minutes, showed a highly porous microstructure by scanning electron microscope, and was morphologically intact in vivo for 14 days after injection. Histological and immunohistochemical analyses and real-time PCR confirmed the chondrogenesis ability of hDPSCs embedded in NC-CS/GP-21 hydrogel.Conclusion: Our results suggest that nanocellulose–chitosan thermosensitive hydrogel is a biocompatible, injectable, mechanically stable and slowly degradable scaffold. hDPSCs embedded in NC-CS/GP-21 hydrogel is a promising, minimally invasive, stem cell-based strategy for cartilage regeneration.Keywords: tissue regeneration, cartilage, scaffolds, stem cells, nanocellulose, chitosan, hydrogel